Rezolvati ecuatiile:
a) 8(2x+3) - 4(5x+1) = 6(-x+5) - 2
b) 5 * [(2x+3) - 2(x+1)] = [4*5(x-1) - 2(4-2x)] + 23
c) 4 * [9-5(x-2)] +3(3x-5) = 2 * [3(x-5) + 17] - 4 .
Multumesc frumos!
MFM:
ma poti lamurii?
Răspunsuri la întrebare
Răspuns de
1
a 16x + 24 -20x +4 = -6x + 30 -2 =
-4x + 28 = - 6x + 28 = \ + 6x
2x + 28 = 28
2x = 0
x= 0
-4x + 28 = - 6x + 28 = \ + 6x
2x + 28 = 28
2x = 0
x= 0
Răspuns de
6
a) 16x+24-20x-4=-6x+30-2
-4x+6x=28-20
2x=8
x=4
b)5(2x+3-2x-2)=(20x-20-8+4x)+23
5.1=24x-28+23
24x=5+5
2x=10
x=5
c) 4.(9-5x+10)+9x-15=2(3x-15+17)-4
76-20x+9x-15=6x+4-4
-11x+61=6x
17x=61
x=61/17
-4x+6x=28-20
2x=8
x=4
b)5(2x+3-2x-2)=(20x-20-8+4x)+23
5.1=24x-28+23
24x=5+5
2x=10
x=5
c) 4.(9-5x+10)+9x-15=2(3x-15+17)-4
76-20x+9x-15=6x+4-4
-11x+61=6x
17x=61
x=61/17
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă